Cartas de estudos de riscos de planícies de inundações e áreas de movimentos de massas: análises e soluções de casos em Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The objective of this work was to identify the sites of risk of major erosion and flooding in the urban area of Manaus, in order to outline the respective containment works to prevent, stabilize and, if possible, reconstitute affected and / or endangered areas. With the growth of the city many places are occupied without proper planning (basic structure of drainage and housing) that influences the factors of origin and / or advancement of existing erosion processes. To begin the research there was a bibliographical survey of geological and geotechnical data bases of the urban area of Manaus, followed for the technical visits to the places of risk. In the first part of the research on mass movements, data collection and tests were carried out for soil characterization, analysis of the drilling data to the percussion that allowed the development of stability studies in some points to determine the appropriate containments for each case. In the second part of the floodplain survey, data were collected on floods from 2001 to 2015 along with reports from CPRM, which monitors the event, and technical visits to flood points in 2015, integration of the existing and collected data allowed the increase of the existing flood margin in literature, proposing adequate solutions and identification of flood points. It was detected the high advance of landslides and mudslides in Manaus, mainly in the north and east, resulting from the increase of inadequate occupations over the years. The areas of risk reached by the floods of the Rio Negro are flood plains occupied by invasions or accumulation of garbage, in the inner part of the city there are numerous occurrences of flooding followed or not by landslides.The distribution of landslides and gullies on the declivity map and technical visits to the sites shows high risk in some neighborhoods and communities, such as Jorge Teixeira 3, Grande Vitória, Nossa Senhora de Fátima, there is an uncontrolled advance of housing in steep and unstructured places. Slope stability studies and the reconnaissance of the flood area showed the innumerable cost containments to the public power, for stabilization and / or reconstitution of the areas. These containments are described separately for the two subjects of risk proposed by the work, thus contributing to the advancement of studies carried out in the demarcation of risk areas, so that in the future an adequate urban advance will be realized with awareness of the risks involved in occupations and poorly performed Works.
Keywords: Deslizamento de terra; Área de risco; Voçorocas; Hidrografia; Erosão de solo; ENGENHARIAS: ENGENHARIA CIVIL